2012
DOI: 10.1530/jme-11-0119
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pattern of oxidative DNA damage and DNA repair in follicular thyroid tumours

Abstract: Increased oxidative stress has been linked to thyroid carcinogenesis. In this paper, we investigate whether oxidative DNA damage and DNA repair differ in follicular adenoma (FA) and follicular thyroid carcinoma (FTC). 7,8-Dihydro-8-oxoguanine (8-OxoG) formation was analysed by immunohistochemistry in 46 FAs, 52 FTCs and 18 normal thyroid tissues (NTs). mRNA expression of DNA repair genes OGG1, Mut Y homologue (MUTYH) and endonuclease III (NTHL1) was analysed by real-time PCR in 19 FAs, 25 FTCs and 19 NTs. Indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 37 publications
0
17
0
4
Order By: Relevance
“…A recent study demonstrated that multinodular thyroid was the most frequent kind of internal tumor in XP-C patients [16], while adenocarcinoma of the thyroid was reported in only one 18-year-old XP-C patient [20]. This might be due to the accumulation of oxidative damage in the thyroid [21]. …”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that multinodular thyroid was the most frequent kind of internal tumor in XP-C patients [16], while adenocarcinoma of the thyroid was reported in only one 18-year-old XP-C patient [20]. This might be due to the accumulation of oxidative damage in the thyroid [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Increased nuclear levels of 8-oxo-dG were found in both benign (human follicular adenomas or FTAs) and malignant (follicular (FTC) and PTC) lesions in comparison with matched normal tissue (Young et al 2010, Karger et al 2012; this most likely reflects the deleterious impact of a long-term exposure to chronic oxidative stress that is observed during thyroid malignancy. Interestingly, an investigation of the link between BER gene expression and human thyroid malignancy showed a reduction in OGG1 expression in FTC compared to FTA (Karger et al 2012). TCGA data analysis highlights a downregulation of the expression level of OGG1 in papillary thyroid tumours with a high level of MAPK1 expression, which reflects the activation of the MAPK signalling pathway ( Fig.…”
Section: Oxidative Dna Damage In Thyroid Carcinomasmentioning
confidence: 93%
“…In mouse models, the levels of oxidative DNA damage in the thyroid gland were higher than those in any other organ, with high levels of thyroid OGG1 mRNA expression (Maier et al 2006). Increased nuclear levels of 8-oxo-dG were found in both benign (human follicular adenomas or FTAs) and malignant (follicular (FTC) and PTC) lesions in comparison with matched normal tissue (Young et al 2010, Karger et al 2012; this most likely reflects the deleterious impact of a long-term exposure to chronic oxidative stress that is observed during thyroid malignancy. Interestingly, an investigation of the link between BER gene expression and human thyroid malignancy showed a reduction in OGG1 expression in FTC compared to FTA (Karger et al 2012).…”
Section: Oxidative Dna Damage In Thyroid Carcinomasmentioning
confidence: 99%
“…Neben der ähnlichen Morphologie ist das Vorliegen identischer Genmutationen ein Argument für die Existenz einer Adenom-Karzinom-Sequenz in der follikulären Karzinogenese. Hingegen unterscheiden sich beide Entitäten in anderen molekulargenetischen Merkmalen, u. a. der antioxidativen Antwort, dem Muster der oxidativen Schädigung und der Aktivierung von Zellzyklus-Checkpoints [15,16,22,33]. 11,19,34,39].…”
Section: Follikuläres Adenomunclassified